SUSTAINABLE ENERGY MANAGEMENT: PRIVATE TRANSPORTATION AND TAXATION - Pearce, Prafula (The journal of contemporary issues in business and government, 2010)
In this article a case is made for the introduction of tax measures that affects sustainable energy use in the transport sector, particularly passenger vehicles in the road transport industry. This article explores whether there is a harmonious relationship between the transportation and tax policy in Australia and whether a change in tax policy is required to promote the use of more fuel efficient vehicles, vehicles using cleaner fuels, a reduction in the use of vehicles and reduction in congestion. The tax should relate to the power and weight of the vehicle and its use and not where the vehicles are manufactured. A new way of thinking is required as the world resource of liquid fuel is being depleted. It takes millions of years for our planet to produce liquid fuel, but it takes an instant to burn it, and once burnt, it is irrecoverable. Therefore, the Australian Government should take the responsibility and implement appropriate taxation policies to promote the efficient movement of people and goods with the least consumption of liquid oil.